Customary Norms, General Principles of International Environmental Law, and Assisted Migration as a Tool for Biodiversity Adaptation to Climate Change - Lavrik, Maksim (Jus Cogens, 2022)
Assisted migration (AM) is a translocation of the representatives of species to areas outside their natural habitats as a response to climate change. This article seeks to identify how customary norms and general principles of international environmental law could guide the development of regulation of AM maximizing the benefits of using AM and minimizing AM-related risks . Among the customary norms and principles of international environmental law discussed in the article and relevant to the regulation of AM are the permanent sovereignty over natural resources, the principle of cooperation, the no-harm rule, the precautionary principle, the principles of prevention, due diligence, and obligation to conduct environmental impact assessment (EIA), the principles of integration and intergenerational equity, common but differentiated responsibilities, and the polluter pays principle, the principles of non-regression, progression, resilience, in dubio pro natura , the principle of ecological proportionality, and the principle of access to information, public participation, and access to justice in environmental matters (principle of good governance, environmental democracy).